Evaluation of Acute Renal Failure After Acinetobacter Baumannii-related Ventilator-associated Event: Routine Data Base Study (Iranian Journal of Kidney Diseases, 2022)
Introduction. Ventilator-associated events (VAEs) are major complications of mechanical ventilation (MV). Herein, we aimed to evaluate whether acute kidney injury (AKI) developed in patients who had been followed up with the diagnosis of Acinetobacter baumannii (AcB)-related VAE, the need for renal replacement therapy (RRT), and its relationship with mortality in patients who developed AKI due to colistin treatment. Methods. A retrospective evaluation of 2,622 patients was conducted. Patients who developed AcB-based VAE and received parental colistin treatment were evaluated in terms of age, sex, diagnosis on intensive care unit (ICU) admission, Acute Physiology and Chronic Health Evaluation (APACHE) II score, colistin dose and treatment duration, duration of ICU stay, AKI staging according to Kidney Disease Improving Global Outcomes criteria, RRT requirement, and mortality. Results. Eighty-five patients (3.19%) had VAEs, of whom 28 (32.9%) had AcB-related VAE. Bacterial eradication was achieved in 14 patients (50%), clinical response was achieved in 14 patients (50%), the mean colistin dose was 298.2 ± 85.5 mg/d, and mean duration of colistin treatment was 14.3 ± 8.6 days. AKI was detected as stages I, II, and III in 28.6%, 14.3%, and 28.6% of the patients; respectively. There was no difference between patients requiring RRT and those who did not in terms of the APACHE II score, bacterial eradication, clinical response to therapy, a daily dose of colistin, treatment duration, and MV duration. Conclusion. Colistin treatment of AcB-related VAE caused AKI in 71.5% of the patients and led to serious conditions in 25% of the patients requiring RRT.  DOI: 10.52547/ijkd.6694